Comparación de la eficacia de dos técnicas de crioterapia para el tratamiento de las verrugas plantares - Chircop, David; Formosa, Cynthia (Revista Internacional de Ciencias Podológicas, 2014)
Objective. To compare two techniques of Cryotherapy for clinical effectiveness, pain, and effect on the quality of life of patients when treating plantar warts. Method. A quasi-experimental matched subject study was conducted. Twenty subjects with a newly diagnosed plantar wart were recruited. Subjects were matched for confounding variables in relation to site of lesion, gender and age, and were divided into two groups. Group A (n=10) were treated using the CO2 Gun & Probe technique whilst Group B (n=10) were treated using the Portable N2O pressurized spray technique. The plantar warts were measured at time 0 (before treatment) and Time 1(3 weeks following treatment) using a metre ruler. The Foot Function Index and the Visual Analog Scale for pain assessment during treatment were also used. Results. The study found no significant difference in the effectiveness (p= 0.387), pain caused during treatment (P=0.855) and FFI scores (p=0.172) for total change in QOL in the study group when comparing both treatments. However, comparison of the mean scores showed that the CO2 Gun & Probe method was slightly more effective in reduction of size. Pain during treatment was almost identical when using both techniques. The FFI scores on all 3 subscales (Pain, Disability and Activity Limitation) showed a larger increase in the CO2 Gun & probe method, when compared to the pressurized N2O Portable device. Conclusions. Although this study has found no significant difference between two different techniques of cryotherapy, mean differences have indicated that the CO2 Gun & Probe technique is more effective in reducing the size of the warts when compared to the N2O Pressurized Spray Technique; however the CO2 Gun & Probe technique caused a larger impact on quality of life. Recommendations from this study suggest that careful consideration is required when selecting a treatment for plantar warts and furthermore patients should be advised on the likely outcomes of each treatment before any intervention.